Pengaruh Tingkat Pendidikan Orang Tua terhadap Kemandirian Mengerjakan Tugas Rumah Siswa Kelas IV SDN Wonosari - Aji Widodo; Ahmad Agung yuwono (Jurnal Sekolah Dasar, 2023)
This study aims to determine the influence parents' education level on independence in doing homework for fourth graders at the Wonosari State Elementary School Temanggung (SD N WONOSARI) in the 2021/2022 school year. This quantitative research use data collection methods in the form of questionnaires and also several surveys of parents of fourth grade students of Wonosari State Elementary School. Questionnaires are used to find out how much independence students have in doing homework. Before being implemented, the instrument had passed the validity stage using the Pearson Product Moment and the reliability test using the Cronbach Alpha formula. while the survey was conducted to find out and also as a means of collecting data on the level of education of parents of students and the analysis in this study was using simple linear regression analysis and for data collection using population research. The results of this study after going through the normality test, linearity test, heteroscedasticity test, hypothesis testing and also the regression coefficient test obtained a simple regression equation as follows: Y = 13,048 + 8,737. X which shows that if the education of parents increases by 1 point, the level of independence will increase by 8.737. There is an influence of the level of parental education on the independence of doing students' homework and the value of R Square = 0.880 results in the calculation reaching a level of 88% of the total number of fourth grade elementary school students. Wonosari country, thas can be proven that there is a significant influence on the level of parental education on the independence of doing homework for fourth graders at Wonosari Elemtary School